A Study of the Movement of Spiritual Awareness - Tumminia, D. author. aut Link
XLII, 231 p.
Keywords: MSIA, the Movement of Spiritual Inner Awareness, has been called the Cadillac of cults. Those interested in new religions may only know of MSIA from these kinds of labels. However, when looked at from a qualitative sociological perspective, a more complex story of religious innovation and cultural change can be told.